Thyroid Nodule Molecular Testing: Is It Ready for Prime Time? - Khan, Tahsin M.; Zeiger, Martha A. (Frontiers in Endocrinology, 2020)
Cytologically indeterminate thyroid nodules remain a diagnostic and clinical challenge, and molecular testing has been advocated and advanced as a diagnostic modality to help guide treatment. While studies have expounded on the improved diagnostic certainty with these tests, data demonstrating meaningful clinical impact and supporting their routine use is still limited at best. In this review, we discuss the limitations regarding diagnostic accuracy, impact on surgical decision-making and outcomes, and cost-effectiveness of molecular testing. By highlighting the limitations of these tests, we aim to promote more thoughtful utilization of these tools in the management of thyroid nodules going forward.